The prevalence of dysphagia and changes in the quality of swallowing in patients infected with COVID-19 (Research, Society and Development, 2022)
Introduction: The emergence of COVID-19 has given rise to research on possible consequences on swallowing and on the quality of swallowing in individuals who were infected by SARS-CoV2. Pulmonary infections, the need for orotracheal intubation, tracheostomy, symptoms, comorbidities, and other factors caused uncertainties about the interference of these factors in the function of swallowing and in quality of life. Objective: To verify the association between the prevalence of swallowing disorders and the quality of life of patients with possible risk factors infected with COVID-19. Methods: This is an observational, analytical, cross-sectional, quantitative study. It was carried out from August to September 2020, in a Hospital in Brasília – DF, with patients hospitalized due to COVID-19 infection. 90 individuals participated in this study; they were adults and elderly with a mean age of 59.9 ± 16.09. Among participants, 55 were men (61.1%) and 35 were women (38.9%) who had a history of swallowing disorders. Data were collected through the analysis of patients' medical records, application of the EAT-10 Test, and the Quality of Life in Swallowing Disorders (SWAL-QOL) validated for Brazilian Portuguese. Results: Considering the scores obtained by the EAT-10 questionnaire, the analysis showed a statistical significance for the variables senescence and tracheostomy (p < 0.05). The analysis of the SWAL-QOL test was performed by domains and showed a statistical significance between the variables senescence, tracheostomy, ageusia, anosmia, and hyporexia. Conclusion: Elderly people infected with COVID-19 and in need of tracheostomy have a greater chance of dysphagia. In addition, factors such as senescence, tracheostomy, age and hyporexia can improve the quality of swallowing in these patients.